In vitro anti-Helicobacter pylori activity of Syzygium aromaticum and the preliminary mechanism of action. (24th April 2022) - Peng, Chang; Sang, Shuyi; Shen, Xue; Zhang, Weijia; Yan, Jiahui; Chen, Pengting; Jiang, Cheng; Yuan, Yuemei; Zhu, Weixing; Yao, Meicun
Abstract: Ethnopharmacological relevance: The dried flower bud of Syzygium aromaticum (L.) Merr. & L.M Perry ( S. aromaticum ) (Myrtaceae), also known as clove, was used in Traditional Chinese Medicine (TCM) to aid gastrointestinal function and treat stomach disorders including vomiting, flatulence and nausea. And it is a food homology medicine which is a promising candidate for H. pylori treatment. H. pylori is a Gram-negative bacterium that infects approximately 50% of the human population worldwide, which is closely related to multiple gastric diseases, including gastric cancer. However, there are still no sufficient studies on the anti- H. pylori activity of S. aromaticum, especially for the mechanism of action. Aim of study: This study aimed to study the antibacterial activities of S. aromaticum extracts on both antibiotic-sensitive and -resistant H. pylori strains, and to explore the underlying mechanisms of action. Materials and methods: The S. aromaticum extracts were obtained by heat reflux extraction and lyophilized to powder form. The phytochemical analyses were performed by High-performance liquid chromatography (HPLC) and UPLC-electrospray ionization mass spectrometry (ESI-MS). In vitro anti- H. pylori activity was evaluated by broth microdilution method. Mechanism of action studies included morphological observation using electron microscopy, determination of expression of virulence genes by reverse transcription quantitative polymerase chain reaction (RT-qPCR), genes expression profile identification by transcriptomic analysis, and exploration of anti- H. pylori infection mechanisms by network pharmacology analysis and western blotting validation. Results: The S. aromaticum extracts, aqueous extract (AE) and 75% hydroalcoholic extract (HE), exerted significant antibacterial activities against both antibiotic-sensitive and -resistant H. pylori strains with MICs of 160∼320 μg/ml, without developing drug resistance. Among them, AE was bactericide to all the tested strains with MBCs of less than 4MIC, while HE was merely bacteriostatic to most of the tested strains with MBCs of 2MIC∼16MIC. Besides, they showed no antagonistic effects in combination with clarithromycin, metronidazole, levofloxacin, and amoxicillin. Additionally, these extracts altered the morphology and ultrastructure and down-regulated the virulence genes expression of H. pylori . And transcriptomic analysis showed that they regulated genes expression of multiple H. pylori biological processes, including tricarboxylic acid cycle (TAC) and pyruvate metabolic pathways. Furthermore, these extracts combated the abnormal activation of PI3K-Akt and MAPK signaling pathways caused by H. pylori infection. Conclusions: Overall, the present study firstly analyzed the chemical compositions of S. aromaticum extracts, and then confirmed their activities on both antibiotic-sensitive and -resistant H. pylori strains. In addition, the mechanisms of action of S. aromaticum extracts against H. pylori were found to be destroying the bacterial structure, down-regulating the expression of virulence genes, and interfering TAC and pyruvate metabolic pathways. Finally, S. aromaticum extracts were found to combated the abnormal activation of PI3K-Akt and MAPK signaling pathways to treat H. pylori infection. This study should accelerate further research and application of S. aromaticum against H. pylori infection. Graphical abstract: Image 1